PERAN KELUARGA DALAM PENDIDIKAN ANAK USIA DINI - FAHRUDDIN, FAHRUDDIN (JURNAL PENDIDIKAN ANAK USIA DINI, 2011)
Family is an informal education that is essential for early childhood education, the integrity of a family, especially mother and father very much needed so that what parents strived to help children internalize the moral values, perceived as a relief to be recognized and understood, precipitated, and personalized in child. children who feel the unity in the family to bear the understanding of the world "parently" parents in the act of abiding morality and intact. That is, the efforts of parents to internalize morality values into the childrens self is not just information, but can be arrested truth. Every parent wants a child who has a good personality. Personality that needs to be fostered and formed. Mother is an adult figure who gave birth to a child, the most longed to have a child who had a good personality. Happiness and prosperity will be enjoyed if the parents successfully foster child with a good personality and grow to form adulthood perfect.Keywords: the role of families, early childhood education